EVALUATION OF STUDENTS USING FRAME MODEL IN TEACHING PHYSICS IN DISTANCE EDUCATION - Khalilov Sarvar Samadovich (Galaxy International Interdisciplinary Research Journal, 2023)
Information technologies are widely used in the teaching of physical and natural sciences in distance education. We will talk about the problems and their solutions in monitoring and evaluating students’ knowledge using the frame model in the teaching of electromagnetic vibrations and waves of physics.